WIP Modulates Oxidative Stress through NRF2/KEAP1 in Glioblastoma Cells - Maribel Escoll; Diego Lastra; Natalia Robledinos-Antón; Francisco Wandosell; Inés María Antón; Antonio Cuadrado (MDPI AG, 2020)
Due to their high metabolic rate, tumor cells produce exacerbated levels of reactive oxygen species that need to be under control. Wiskott-Aldrich syndrome protein (WASP)-interacting protein (WIP) is a scaffold protein with multiple yet poorly understood functions that participates in tumor progression and promotes cancer cell survival. However, its participation in the control of oxidative stress has not been addressed yet. We show that WIP depletion increases the levels of reactive oxygen species and reduces the levels of transcription factor NRF2, the master regulator of redox homeostasis. We found that WIP stabilizes NRF2 by restraining the activity of its main NRF2 repressor, the E3 ligase adapter KEAP1, because the overexpression of a NRF2ΔETGE mutant that is resistant to targeted proteasome degradation by KEAP1 or the knock-down of KEAP1 maintains NRF2 levels in the absence of WIP. Mechanistically, we show that the increased KEAP1 activity in WIP-depleted cells is not due to the protection of KEAP1 from autophagic degradation, but is dependent on the organization of the Actin cytoskeleton, probably through binding between KEAP1 and F-Actin. Our study provides a new role of WIP in maintaining the oxidant tolerance of cancer cells that may have therapeutic implications.